ANTIOXIDANT ACTIVITY IN THE FOUR SPECIES OF CYANOBACTERIA ISOLATED FROM A SULFUR SPRING IN THE WESTERN GHATS OF KARNATAKA - K. SHARATHCHANDRA; M. RAJASHEKHAR (International Journal of Pharma and Bio Sciences, 2013)
In the present study, efforts were made to reveal the total phenolics and flavanoid contents and antioxidant activity in the four cyanobacterial species viz., Phormidium fragile, Lyngbya limnetica, Scytonema bohnerii and Calothrix fusca isolated from a sulfur spring in the Western Ghats of Karnataka. The cultures were maintained in BG11 medium. In vitro screening for antioxidant activity of ethanol and methanol extracts of these cultures was determined by total antioxidant capacity by phosphomolybdenum, DPPH free radical scavenging and ferric ion reducing assays. The study indicates the significant antioxidant potential in Lyngbya limnetica (P<0.01) followed by Scytonema bohnerii (P<0.05) and least activity was observed in Calothrix fusca (P>0.05). Therefore, mass cultivation of such strains for the production of valuable bioproducts may be a good strategy for future use. The study has revealed the utilization of certain strains of cyanobacteria for the production of biologically active compounds particularly, antioxidants.